Modernisation of the IT occupations in the age of 4.0 - Schwarz, Henrik [Verfasser]; Conein, Stephanie [Verfasser]; Tutschner, Herbert [Verfasser] (My University, 2017)
"BIBB has been investigating whether the four dual IT occupations, which have remained unchanged since 1997, need to be modernised. Against the background of the increasing digitalisation of the world of work, the aims of this process were to identify current and foreseeable requirements for skilled IT staff and to draw up proposals for the future shaping of the IT oc-cupations. This article presents selected outcomes of the investigation and uses this to arrive at conclusions with regard to a possible rearrangement of IT occupations." (author's abstract ; BIBB-Doku)
Modernisierung der IT-Berufe in Zeiten von VierPunktNull
Keywords: G 2.2.1 Technologisierung; S 6.4.9 IT-Berufe; S 6.4.1.2 Dienstleistungskaufleute; Industrie 4.0; Technisierung; IT-Systemelektroniker; IT-Systemkaufmann; Fachinformatiker Anwendungsentwicklung; Fachinformatiker Systemintegration; Informatikkaufmann; Berufsbild; Neuordnung der Ausbildungsberufe; Qualifikationsanforderung